Optimizing Digital Pedagogy in Education: Exploring Human Resource Management Approaches - A'yun, Qurroti; Awalluddin; Hasan, Ahmad Makki (Mimbar Ilmu, 2024)
Digital transformation in education has become an urgent necessity in response to technological advancements and 21st-century learning demands. However, the optimization of digital pedagogy in educational institutions still faces various challenges, particularly in human resource management (HRM). The limited readiness of educators to effectively utilize digital technology may hinder the implementation of innovative learning processes. This study aims to explore HRM approaches that support the optimization of digital pedagogy in educational institutions. This research employs a literature review method, analyzing relevant sources on HRM and digital pedagogy. Data were collected through document studies consisting of academic journals, books, and research reports addressing HR management in the education sector within the context of digital transformation. Data analysis was conducted using qualitative descriptive methods with content analysis to identify key concepts, main themes, and best practices in implementing HRM to support digital pedagogy. The findings reveal that a structured HRM approach can enhance educators' competencies in using digital technology and foster an innovative and adaptive learning ecosystem. The HRM approach includes identifying digital training needs, developing continuous training programs, supporting the use of digital learning tools, implementing digital performance evaluations, and recognizing outstanding educators. This study concludes that effective HR management is a key driver in optimizing digital pedagogy, ultimately improving the quality of education in the digital era.